1969
DOI: 10.1002/1097-0142(196905)23:5<1221::aid-cncr2820230532>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cancer of the uterine cervix in north India

Abstract: Cancer of the uterine cervix is the most common malignant tumor among women in India. T h e varying frequency of cervix carcinoma in different parts of the country is dependent upon certain environmental factors, such as socioeconomic conditions, sexual experience, age a t marriage, fertility, and penile hygiene. This paper is based upon a clinical and statistical analysis of 693 cases of cervix carcinoma diagnosed from a population study of 39,587 women who were screened by vaginal smear examination. T h e fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Severity of lesions increased with increasing parity indicating that trauma and child birth are predisposed to cervical lesions. The results of our study correlate with that of Rohtagi and Wahi et al [4, 5]. CIN III and carcinoma were found in 52.2% of patients which belonged to a lower socioeconomic status, whereas only 13.3% belonged to higher socioeconomic status which was in concordance with the study conducted by Sankaranarayanan et al who found that 8% of their cases was a from higher socioeconomic group [6].…”
Section: Discussionsupporting
confidence: 92%
“…Severity of lesions increased with increasing parity indicating that trauma and child birth are predisposed to cervical lesions. The results of our study correlate with that of Rohtagi and Wahi et al [4, 5]. CIN III and carcinoma were found in 52.2% of patients which belonged to a lower socioeconomic status, whereas only 13.3% belonged to higher socioeconomic status which was in concordance with the study conducted by Sankaranarayanan et al who found that 8% of their cases was a from higher socioeconomic group [6].…”
Section: Discussionsupporting
confidence: 92%
“…This study was carried out on 30 cases of OSCC which were classified according to WHO classification system 9 as well differentiated (11 cases), moderately differentiated (11 cases), and poorly differentiated (8 cases). The results showed that the age among the studied cases ranged from 23-88 years with a mean age of 61.37± 14.9 with a male to female ratio of 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical cancer is the second most common cancer among women in the world after breast cancer and is the most common cancer among Indian women [14]. A number of treatment modalities are being used for the treatment of the disease.…”
Section: Purposementioning
confidence: 99%